The Correlates of Entrepreneurship in Three Types of Firms - Miller, Danny (Management Science, 1983)
The objective of the research was to discover the chief determinants of entrepreneurship, the process by which organizations renew themselves and their markets by pioneering, innovation, and risk taking. Some authors have argued that personality factors of the leader are what determine entrepreneurship, others have highlighted the role played by the structure of the organization, while a final group have pointed to the importance of strategy making. We believed that the manner and extent to which entrepreneurship would be influenced by all of these factors would in large measure depend upon the nature of the organization. Based upon the work of a number of authors we derived a crude typology of firms: Simple firms are small and their power is centralized at the top. Planning firms are bigger, their goal being smooth and efficient operation through the use of formal controls and plans. Organic firms strive to be adaptive to their environments, emphasizing expertise-based power and open communications. The predictiveness of the typology was established upon a sample of 52 firms using hypothesis-testing and analysis of variance techniques. We conjectured that in Simple firms entrepreneurship would be determined by the characteristics of the leader; in Planning firms it would be facilitated by explicit and well integrated product-market strategies, and in Organic firms it would be a function of environment and structure. These hypotheses were largely borne out by correlational and multiple regression analyses. Any programs which aim to stimulate entrepreneurship would benefit greatly from tailoring recommendations to the nature of the target firms.